COMPETING CURRENCIES AS AN ALTERNATIVE SCENARIO TO LEGAL TENDER CLAUSE MATHEMATICAL PROOF - Gawthorpe, Kateřina; Stroukal, Dominik, 1987-; Nikolovová, Pavla, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
Previous literature examining the scenario without the constraint of legal tender law is a rather theoretical analysis of the subject matter. Aside from the theoretical examination of the competition of money this paper offers dynamic structural macroeconomic model based on the money in the utility function. This model compares the current monetary conditions with the potential situation permitting more currencies circulating alongside. The main assumption about individuals' preferences over stable currencies underlines the whole paper with emphasis on the mathematical model. The uniqueness of this model lies in the incorporation of variables affecting respective money demand functions into the utility function of the DSGE model and in the purpose of its use as well as its variables, where representative agent is a household owning a bank rather than a firm. Overall the results of this paper favor the idea of exclusion of the legal tender law in a developed country without severe turmoil. Particularly, the ascent of competition among currencies leads to lower inflation than present scenario. However, final simulations of the model in Matlab supplements such so far "unambiguous" view with skepticism due to possible difficulties during discovery process in such scenario.
Vedoucí práce: Dominik Stroukal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses